Strategi Pengemasan dan Pemasaran Produk Desa Wisata: Studi Kasus di Desa Tegaljadi - Ni Desak Made Santi Diwyarthi; Putu Diah Sastri Pitanatri; Nyoman Gede Mas Wiartha; Ni Wayan Chintia Pinaria (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Community-based tourism encourages tourism villages to enhance the competitiveness of local products through more innovative packaging and marketing strategies. However, most entrepreneurs in Tegaljadi Village, Tabanan Regency, continue to face limitations in product packaging, brand identity development, and the utilization of digital media as promotional tools. This community service program aimed to improve entrepreneurs’ knowledge and understanding of product packaging and digital marketing to support sustainable tourism village development. The program was conducted from March to April 2026 and involved five MSME owners as a pilot project group. A participatory approach was employed through several stages, including observation, socialization, demonstrations, practical activities, and evaluation. The results indicate that participants’ average level of understanding increased from 2.80 to 4.19, representing an improvement of 49.64%. Furthermore, 80% of the participants began utilizing social media as a promotional tool, while 80% successfully developed stronger product identities through improved packaging designs and labeling. The program also fostered collaboration between MSME actors and the local community in promoting natural honey, traditional Balinese coffee, and jaje kaliadrem as flagship products of the tourism village. These findings suggest that community-based socialization can serve as an effective strategy for enhancing the capacity of local entrepreneurs while strengthening the long-term competitiveness of tourism villages.